(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Education is an important instrument for social and economic change and an investment for better future. It is a lifelong process. It should cater to the needs of those who need to further knowledge and skills for various reasons. Distance Education is an innovative and flexible system for imparting education to varied target groups at different stages. At present, the youth and women are enrolling in higher number into Distance mode.